2021
DOI: 10.1016/j.tacc.2020.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Challenges faced in establishing a dedicated 250 bed COVID-19 intensive care unit in a temporary structure

Abstract: An Intensive Care Unit (ICU) is an organized system for the provision of care to critically ill patients that provides intensive and specialized medical and nursing care, an enhanced capacity for monitoring, and multiple modalities of physiologic organ support to sustain life during a period of life-threatening organ system insufficiency. While this availability of trained manpower and specialized equipment makes it possible to care for critically ill patients, it also presents singular challenges in the form … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 19 publications
3
10
0
Order By: Relevance
“…Results from our multivariate analysis on 573 patients, found that Age, Neutrophil percentage, and DM status were most associated with COVID-19 severity. Further, results from the Cochran-Mantel-Haenszel test on the entire cohort of 813 patients, while controlling for age as a confounder, confirmed findings from previous analyses and meta-analyses [ [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , s[27] ] that DM is a significant contributor to COVID-19 severity and mortality. Our results agree with the meta-analysis Kumar et al showing that DM was associated with a significant increase in COVID-19 severity (OR of 2.75) and mortality (OR of 1.90) [ 25 ] with similar Odds-ratios.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Results from our multivariate analysis on 573 patients, found that Age, Neutrophil percentage, and DM status were most associated with COVID-19 severity. Further, results from the Cochran-Mantel-Haenszel test on the entire cohort of 813 patients, while controlling for age as a confounder, confirmed findings from previous analyses and meta-analyses [ [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , s[27] ] that DM is a significant contributor to COVID-19 severity and mortality. Our results agree with the meta-analysis Kumar et al showing that DM was associated with a significant increase in COVID-19 severity (OR of 2.75) and mortality (OR of 1.90) [ 25 ] with similar Odds-ratios.…”
Section: Discussionsupporting
confidence: 79%
“…Study design: This is a retrospective study record-based that was conducted at a newly raised COVID-19 dedicated hospital under PM Cares fund in New Delhi, namely, Sardar Vallabh Bhai Patel COVID Hospital [ 19 ]. The study period was from July 13, 2020 to October 14, 2020.…”
Section: Methodsmentioning
confidence: 99%
“…Another 51% of the articles specified the name and/or the type of health organisations they were focussed on. 17 , 18 , 19 , 20 , 21 , 23 , 26 , 27 , 28 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 43 , 45 , 46 , 47 , 48 , 49 , 53 , 54 , 55 , 56 , 57 , 59 , 60 , 61 , 62 , 63 , 64 , 66 All of the remaining studies did not specify a health organization of focus or concentrated on groups of respondents within health organisations.…”
Section: Resultsmentioning
confidence: 99%
“…These were erected in sports stadiums [47,66], parking lots [67] and public parks (e.g., Central Park, New York, NY, USA) [46]. Examples for these come from countries as diverse as Argentina [66], Brazil [66], France [66] and India [68].…”
Section: Temporary Emergency Hospitalsmentioning
confidence: 99%